The Impact of Numeracy on Early Childhood Development: A Meta-Analysis of Experimental Studies - Hidayah, Fitri Nur; Retnawati, Heri (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study employs a meta-analytic approach to assess the impact of numeracy on early childhood development. Analyzing 41 experimental studies, the research aggregates data to provide a precise estimate of numeracy's effect size, enhancing the generalizability of findings. A random-effects model was utilized due to the high heterogeneity among studies (I² = 91.32%), indicating significant variability across different geographical regions, sample sizes, and intervention durations. The results demonstrate a statistically significant positive effect of numeracy on early childhood abilities, with a coefficient estimate of 0.56834 (p < 0.001). Despite the strong evidence supporting early numeracy interventions, the study highlights the need for context-specific approaches to maximize effectiveness. The analysis also reveals the presence of publication bias, as indicated by funnel plot symmetry and a fail-safe N of 7,159, suggesting robust findings. Future research should address the observed variability and further explore the contextual factors influencing the success of early numeracy programs.